Ca(2+) influx via the L-type Ca(2+) channel during tail current and above current reversal potential in ferret ventricular myocytes - Zhou, Zhuan (Blackwell Science Inc, 2000)
1. Current through L-type Ca(2+) channels (I(Ca)) was measured electrophysiologically at the same time as Ca(2+) influx was measured by trapping entering Ca(2+) with a high concentration of indo-1 (> 1 mm) in ferret ventricular myocytes. 2. Na(+)-free conditions prevented Na(+)–Ca(2+) exchange and K(+) currents were blocked by Cs(+) and TEA. Thapsigargin (5 μm) prevented Ca(2+) uptake and release by the sarcoplasmic reticulum. I(Ca) was pre-activated by brief pulses to +120 mV (the equilibrium potential for Ca(2+), E(Ca)), followed by steps to different membrane potentials (E(m), −80 to +100 mV), in some cases in the presence of the Ca(2+) channel agonist FPL-64176. 3. Integrated I(Ca) (I(Ca)) was linearly related to the change in the concentration of Ca(2+) bound to indo-1, which was assessed by the fluorescence difference signal ΔF(d) (F(d) = F(500)–F(400)). This created an internal calibration of ΔF(d) as a measure of Ca(2+) influx. 4. The ΔF(d)/I(Ca)dt relationship was virtually unchanged at all measurable inward I(Ca) (at E(m) from −80 to +50 mV). This indicates that the fractional current carried by Ca(2+) and channel selectivity are unchanged over this E(m) range, and also that the selectivity for Ca(2+) is very high. 5. Ca(2+) influx was readily detected by ΔF(d) beyond the I(Ca) reversal potential (+65 to +100 mV) and was not abolished until E(m) was +120 mV (i.e. E(Ca)). This is explained by the fact that inward Ca(2+) flux at the I(Ca) reversal potential is exactly balanced by outward Cs(+) current through the Ca(2+) channels and can be described by classic Goldman flux analysis with a Ca(2+)/Cs(+) selectivity of the order of 5000. 6. This result also emphasizes that net Ca(2+) influx via Ca(2+) channels occurs over a voltage range where the net channel current is outward.